Bioremediation: Fabricating Bioactive 3D Metal–Organic Framework Devices (Adv. Sustainable Syst. 12/2020). (8th December 2020) - Singh, Ruhani; Souillard, Guillaume; Chassat, Lucile; Gao, Yuan; Mulet, Xavier; Doherty, Cara M.
Abstract : In article number 2000059, Cara M. Doherty and co‐workers fabricate a 3D metal‐organic framework (MOF) device for continuous environmental sensing and pesticide remediation. The key features of the technology are a cutting‐edge static mixer, developed for flow chemistry applications onto which they performed an in‐situ growth of porous ZIF‐8 MOF encapsulating the organophosphate degrading enzyme (OpdA). The combination of these approaches allows both structural and spatial securement of the enzyme whilst imparting functionality which can be monitored in real‐time over several days.